PENGARUH PROFESIONALISME DAN OBJEKTIFITAS AUDITOR TERHADAP KETEPATAN PEMBERIAN OPNI AUDIT - Hari Stiawan (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
The purpose of this research is to find out how much influence the professionalism and objectivity of the auditor on the accuracy of giving opinion to the Public Accountant in the South Jakarta , both partially and simultaneously. This type of research is causality, using primary data through distributing questionnaires to KAP in the South Jakarta. Respondents are auditors, Sampling was done by random sampling method, The unit of analysis is the auditor, as well as data analysis using multiple linear regression analysis. The results showed that simultaneously the variables of professionalism and objectivity had a significant effect on the accuracy of the provision of audit opinions. Partially, it shows that the professionalism and objectivity variables influence significantly on the accuracy of the provision of audit opinions, adjusted R square 65.5%, the remaining 34.5% is influenced by other variables.